Projected climate adaptation benefits of One CGIAR - Ramírez Villegas, Julián Armando; Rosentock, Todd; Steward, Peter R.; Thornton, Philip K.; Loboguerrero Rodriguez, Ana María; Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In the present analysis, we first create a projection of the number of beneficiaries (rural individuals and households) in climate hazard areas using geospatial datasets on climate hazards and rural population. We find that: (1) By 2030, CGIAR’s work on climate adaptation is projected to benefit 234 million rural people in 59 million rural households in regions facing significant climate hazards. (2) Some 66% of the projected individual beneficiaries are in SA (34%) and SEA (32%). India (26%) and China (24%) alone account for about 50% of beneficiaries globally. Approximately 15% are in SSA, equally divided between ESA and WCA; the remaining beneficiaries are in LAC (7%) and CWANA (11%). (3) Adoption of climate-smart agricultural practices, climate-adapted varieties, and climate-related advisory services will increase productivity by an average of 24 % and, in at least 62% of cases, will also reduce interannual yield variability. Despite these significant potential upside gains, changing farming practices also carries production risk. (4) Scaling up both improved varieties and improved agronomy could more than double economic benefits as compared to improved varities alone; this suggests that integrative programs that bundle several innovations have the potential to amplify impact.